Digital Literation Models Development Based School Culture to Improve Students' Life Skill in the 21st Century - Mandra Saragih; Habib Syukri Nst; Rita Harisma; Ismail Hanif Batubara (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to develop digital literacy model through a school culture-based. Digital literacy was chosen considering the development of information through digital media. This study used Research and Development (RD). The research step was to collect data and design a product in a literacy model design based on school culture. The components of developing a school culture-based digital literacy model consist of participants, select participants, a digital literacy program in the form of training, the content of digital literacy programs in the form of exercise, media, teaching materials, assessment, program socialization, implementation, evaluation and mentoring. This research is the design of a guideline for implementing a school culture-based digital literacy model that can be used in digital literacy activities in schools.